1988
DOI: 10.1007/bf01735377
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilaments are spaced randomly in the radial dimension of axons

Abstract: The organization of the cytoskeleton is compared in the large myelinated parasympathetic and somatic motor axons of the avian oculomotor system. Electron microscopic studies demonstrate that neurofilaments are the chief structural elements in these axons, and quantitative analyses of the distribution of neurofilaments in axonal cross-sections found that the average neurofilament packing density is 25% greater in the parasympathetic axons than in the somatic motor axons. In both types of axon the distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 17 publications
6
52
0
Order By: Relevance
“…Although modest differences in axonal NF density (,'025 %) have been reported among different populations of neurons (Price et al, 1988) and in different regions of small-caliber nerve fibers (Nixon and Logvinenko, 1986;Parhad et al, 1987), greater variations of NF density are not normally observed. The alterations in axonal NF content associated with somatofugal axonal atrophy (where NF content decreases) and with normal postnatal development (where NF content increases) correlate with changes in axonal cross-sectional area, rather than changes in NF density (Friede and Samorajski, 1970;Hoffman et al, 1984;Hoffman et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…Although modest differences in axonal NF density (,'025 %) have been reported among different populations of neurons (Price et al, 1988) and in different regions of small-caliber nerve fibers (Nixon and Logvinenko, 1986;Parhad et al, 1987), greater variations of NF density are not normally observed. The alterations in axonal NF content associated with somatofugal axonal atrophy (where NF content decreases) and with normal postnatal development (where NF content increases) correlate with changes in axonal cross-sectional area, rather than changes in NF density (Friede and Samorajski, 1970;Hoffman et al, 1984;Hoffman et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…Considerable evidence now suggests that these tracks are microtubules (Shah et al, 2000;Wagner et al, 2004;Francis et al, 2005;He et al, 2005). Thus, it is interesting to note that morphometric studies on axonal cytoskeletons in vivo have demonstrated that neurofilaments generally outnumber microtubules, at least in large myelinated axons, with estimates of the neurofilament/ microtubule ratio ranging from 7/1 to 97/1, depending on the neuronal cell type (Price et al, 1988;Reles and Friede, 1991). In these axons, it is clear that not all neurofilaments can be adjacent to a microtubule.…”
Section: Discussionmentioning
confidence: 99%
“…In each case, systematic sampling of nonoverlapping fields resulted in sampling 50 -80% of the total myelinated fibers in each nerve. Neurofilament density and number in the sural nerve were calculated as previously described (27). Thin sections (60 nm) were cut with a diamond knife and stained with uranyl acetate and bismuth subnitrate before being viewed with a Zeiss 10 electron microscope operated at 80 keV.…”
Section: Methodsmentioning
confidence: 99%